Penguatan Nilai Toleransi Melalui Pendidikan Multikultural di SDN Bululawang 02 - Siska Afriyanti A; Silvy Nur A; Wafda Aufa A (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
This study aims to describe the implementation of multicultural education at SDN Bululawang 02 and to identify the supporting and inhibiting factors of its implementation. The research employs a qualitative approach with a descriptive method. The subjects of the study consist of the principal and teachers. Data collection techniques were conducted through semi-structured interviews, while data analysis used an interactive analysis model that includes data reduction, data display, and conclusion drawing. The results of the study indicate that multicultural education has been implemented through school policies, the learning process, and school culture. The school applies deep learning-based instruction that emphasizes meaningful learning experiences with the support of learning technologies such as smart TVs and smart boxes. Multicultural education is also realized through various religious, social, and national activities, such as routine religious activities, the commemoration of national and religious holidays, as well as the use of traditional clothing, which serve to instill values of tolerance, togetherness, and mutual respect. The role of the school principal is evident through classroom supervision, teacher training, and learning evaluation, while teachers integrate multicultural values through varied and enjoyable teaching methods. The challenges faced include the diverse characteristics of students, limited facilities, and differences in students' academic abilities. Efforts made by the school to overcome these challenges involve collaboration with parents and adjustments to learning strategies. This study concludes that multicultural education in elementary schools has been implemented well; however, it still requires strengthening in terms of facility support, teacher competence, and ongoing collaboration between schools and parents.